Chalcopyrite dissolution rate law from pH 1 to 3 - P. ACERO; J. CAMA; C. AYORA; M.P. ASTA (Geologica Acta, 2009)
Chalcopyrite dissolution kinetics in the pH range of 1 to 3 were studied by means of long-term flow-through experiments to obtain a dissolution rate law which can be coupled with reactive transport models to forecast Acid Rock Drainage. In the range of conditions under study, the rate of chalcopyrite dissolution is only slightly dependent on hydrogen ion activity, increasing with decreasing pH. The steady-state dissolution rates obtained in the present study were combined with earlier results presented by Acero et al. (2007a) to obtain the following expression for chalcopyrite dissolution rate law: where Rchalcopyrite is the chalcopyrite dissolution rate (mol m-2 s-1), aH+ is the activity of hydrogen ion in solution, R is the gas constant (kJ mol-1 K-1) and T is the temperature (K). This expression can applied through a wide range of environmental conditions similar to the ones found in systems affected by acid drainage. In agreement with earlier chalcopyrite kinetic studies, iron was released to solution preferentially over copper and sulfur, compared with the stoichiometry of the pristine mineral. Consistently, XPS examination of the samples showed that reacted surfaces were enriched in sulfur and copper (relative to iron) compared with the initial, pristine chalcopyrite surface. However, this surface layer does not exert any passivating effect on chalcolpyrite dissolution and the kinetics of the overall process in the long term seems to be surface-controlled.